2020
DOI: 10.5713/ajas.19.0452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three different diets on the fatty acid profile and sensory properties of fresh Pecorino cheese “Primo Sale”

Abstract: Objective: This study aimed to evaluate and compare the effects of three different diets on the fatty acids (FA) profile and sensory properties of a characteristic Italian fresh cheese: Pecorino "Primo Sale” (PS).Methods: Fifty-four sheep were divided into three feeding groups: total mixed ration (TMR) enriched with extruded linseed (TL), control diet with TMR without any integration (TC), and pasture (P). During cheese production, six cheeses per experimental group were produced each week, stored for 10 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In the present study, the TBARS were generally low and within acceptable ranges and not significantly different among groups. This is in accordance with the results of Fusaro et al (2020) who also found no differences in TBARS concentrations in cheeses in a very similar experiment [ 66 ]. This finding is an expected one, since the overall fat content was not significantly different among groups, implying that similar levels of fat oxidations occurred in the curds.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the TBARS were generally low and within acceptable ranges and not significantly different among groups. This is in accordance with the results of Fusaro et al (2020) who also found no differences in TBARS concentrations in cheeses in a very similar experiment [ 66 ]. This finding is an expected one, since the overall fat content was not significantly different among groups, implying that similar levels of fat oxidations occurred in the curds.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the highly degradable nitrogen and fiber of fresh forage along with a higher rumen pH related to grazing activity may promote the rumen bacteria producing CLA cis -9, trans -11 while inhibiting the biohydrogenation of C18:1 trans -11, which is converted to CLA cis -9, trans -11 via Δ9-desaturase in the mammary gland [ 47 ]. Although several studies investigated FA composition of ewe milk fat as influenced by the season of production, the literature on pecorino cheese is limited [ 15 , 16 , 17 , 48 , 49 , 50 , 51 ]. The use of vegetable seeds and oils [ 52 , 53 , 54 , 55 , 56 , 57 ] led to changes in fatty acid composition of ewe milk and cheese higher than those we observed.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, no studies regarding the addition of citrus EOs to ewes’ milk cheeses are present in the literature. Generally, Sicilian fresh-pressed cheese made from ewes’ milk are referred to as Pecorino “Primosale” cheeses [ 20 ], which are commonly consumed after a very short ripening time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%